La precarización laboral de los Servidores Públicos con nombramientos provisionales. - Enriquez Guayanay, Luis Alejandro (2023)
In the present research work, I can state that I deal with the precariousness that exists by provisional appointments, the same one that was established that with this type of hiring that are provisional appointments, currently they have resulted in precariousness work of the public servants, for which reason it has become one of the most used tools, thus violating a number of rights, making it clear that in order to make a provisional appointment there must be a position created within the public institution and the person can continue to hold the position. same until being called to contest of merits and opposition and only the winner of said contest will receive the definitive appointment, according to what is expressed by the Constitutional Court. In addition, due to the above, it has resulted in a multitude of what could be called large- scale protection actions by the plaintiffs and despite the fact that these are restored by competent judicial units, for the same reason that there is uncertainty or lack of guarantee on jobs, thus showing an inconvenience in the administration of each public institution.